Map of part of Manitoba and North West Territory showing subdivided into townships that portion in which the Hudson's Bay Co . - Aldous, Montague (Surveyor); Burland Lithographic Company (Lithographer)
This is a map of land distribution in Manitoba and the Northwest Territories at the end of 19th century. It consists of two parts: part 1 - general map of the region showing inspected lands and Hudson's Bay Company's and Indian reserves; and part 2 - Hudson's Bay Company's information on cities, farming, lands, climate, municipal organization, schools, timber and fuel industries, transportation and communication in Manitoba and the Northwest Territories [see also record for part 1]. Includes information on cities, farming, lands, climate, municipal organization, schools, timber and fuel industries, transportation and communication in the region. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .